The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep37627
|View full text |Cite|
|
Sign up to set email alerts
|

Oligofructose as an adjunct in treatment of diabetes in NOD mice

Abstract: In type 1 diabetes, restoration of normoglycemia can be achieved if the autoimmune attack on beta cells ceases and insulin requirement is met by the residual beta cells. We hypothesize that an adjunctive therapy that reduces insulin demand by increasing insulin sensitivity will improve the efficacy of an immunotherapy in reversing diabetes. We tested the gut microbiota-modulating prebiotic, oligofructose (OFS), as the adjunctive therapy. We treated non-obese diabetic mice with an immunotherapy, monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Nevertheless, in some animal studies reduction of fat mass was achieved without significant body weight changes (Roberfroid et al, 2010). Treatments with prebiotics are frequently associated to fasting glycemia, glucose tolerance and insulin sensitivity improvement (Everard et al, 2011; Pachikian et al, 2013; Chan et al, 2016). Focusing on liver functionality, prebiotics have shown its capacity to modulate lipid metabolism.…”
Section: Modulation Of Intestinal Microbiotamentioning
confidence: 99%
“…Nevertheless, in some animal studies reduction of fat mass was achieved without significant body weight changes (Roberfroid et al, 2010). Treatments with prebiotics are frequently associated to fasting glycemia, glucose tolerance and insulin sensitivity improvement (Everard et al, 2011; Pachikian et al, 2013; Chan et al, 2016). Focusing on liver functionality, prebiotics have shown its capacity to modulate lipid metabolism.…”
Section: Modulation Of Intestinal Microbiotamentioning
confidence: 99%
“…Preclinical studies have demonstrated that a diet containing inulin can ameliorate IR in diabetic mice [16]. Oligofructose can reduce lymphocytic infiltrate into the pancreatic islets, increase the β -cell proliferation rate to improve insulin sensitivity and β -cell function [17]. The review of clinical trials also suggests that ITC supplementation has beneficial effects on metabolic syndrome in individuals with T2DM [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such protective effects of hydrolyzed casein diets are believed to be due to improved permeability of the gut epithelium by the peptides contained in the diets . Although earlier studies did not show pronounced effects for the prebiotic oligofructose in diabetes prevention in an animal model, its dietary supplementation as adjunct with anti‐CD3 antibody therapy resulted in higher rate of diabetes remission, with significant improvements in β‐cell function, in NOD mice compared with mice receiving anti‐CD3 antibody only . A randomized clinical trial involving 34 healthy participants who received the natural prebiotic inulin‐type fructans (ITFs) daily for 3 weeks revealed improved GIT functions with a relative increase in Bifidobacterium species compared with the controls .…”
Section: Modulation Of Gut Microbiome For Treatment Of T1dmentioning
confidence: 99%
“…136 Although earlier studies did not show pronounced effects for the prebiotic oligofructose in diabetes prevention in an animal model, 137 its dietary supplementation as adjunct with anti-CD3 antibody therapy resulted in higher rate of diabetes remission, with significant improvements in β-cell function, in NOD mice compared with mice receiving anti-CD3 antibody only. 138 A randomized clinical trial involving 34 healthy participants who received the natural prebiotic inulin-type fructans (ITFs) daily for 3 weeks revealed improved GIT functions with a relative increase in Bifidobacterium species compared with the controls. 139 Female NOD mice fed diets supplemented with 5% long-chain ITFs, but not short-chain ITFs, for 24 weeks showed a decreased incidence of T1D that was associated with changes in pancreatic-gut immune responses and gut barrier function.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%